Last post - Arthur, Max 1939- (Phoenix, 2005)
From the author of the bestselling Forgotten Voices of the Great War comes a final look at the last 21 living British veterans of the First World War. These interviews, conducted in 2004, will never be repeated, as the youngest was 106 years old, and most are now gone. These first-person accounts follow the young soldiers from their homes throughout Britain to the raging battles while in the service of the Royal Field Artillery, Black Watch, Royal Navy, and others. These combat experiences should never be forgotten.